2019
DOI: 10.1017/s0007114519003039
|View full text |Cite
|
Sign up to set email alerts
|

The effects of myo-inositol and probiotic supplementation in a high-fat-fed preclinical model of glucose intolerance in pregnancy

Abstract: Glucose intolerance during pregnancy – a major driver of gestational diabetes mellitus (GDM) – has significant short- and long-term health consequences for both the mother and child. As GDM prevalence continues to escalate, there is growing need for preventative strategies. There is limited but suggestive evidence that myo-inositol (MI) and probiotics (PB) could improve glucose tolerance during pregnancy. The present study tested the hypothesis that MI and/or PB supplementation would reduce the risk of glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…Myo-inositol treatment in the genetically-modified db/þ mouse model of GDM reduced maternal intra-abdominal, gonadal and perirenal adiposity, but had no apparent effect on fetal size (Plows et al 2017). In contrast, in a high fat diet mouse model of GDM, myo-inositol treatment did not affect maternal glycemia or fat accretion (Plows et al 2020), but did increase maternal adipose tissue mRNA expression of Ir, Irs1, Akt2, and Pck1, which are all key members of the insulin signaling pathway, and demonstrated an associated decrease in offspring birthweight (Plows et al 2020). This suggests that inositol might have a pro-insulin or an insulin-like effect in adipose tissue resulting in decreased maternal lipid mobilization and lipid transfer for fetal growth.…”
Section: Dysregulated Maternal-placental-fetal Lipid Metabolism Adipcontrasting
confidence: 60%
“…Myo-inositol treatment in the genetically-modified db/þ mouse model of GDM reduced maternal intra-abdominal, gonadal and perirenal adiposity, but had no apparent effect on fetal size (Plows et al 2017). In contrast, in a high fat diet mouse model of GDM, myo-inositol treatment did not affect maternal glycemia or fat accretion (Plows et al 2020), but did increase maternal adipose tissue mRNA expression of Ir, Irs1, Akt2, and Pck1, which are all key members of the insulin signaling pathway, and demonstrated an associated decrease in offspring birthweight (Plows et al 2020). This suggests that inositol might have a pro-insulin or an insulin-like effect in adipose tissue resulting in decreased maternal lipid mobilization and lipid transfer for fetal growth.…”
Section: Dysregulated Maternal-placental-fetal Lipid Metabolism Adipcontrasting
confidence: 60%
“…It is related to obesity and IR, and hyperleptinemia is frequent in HFD-fed animal models [ 53 , 91 ]. In preclinical trials, pA1c and other probiotic supplementations [ 53 , 92 , 93 ] significantly reduced circulating leptin levels, while other studies did not report significant changes [ 87 , 94 ], and evidence from human studies is weak [ 95 ]. Previously, in vitro experiments in human and animal cell lines showed that leptin induces GLP-1 production [ 96 ], which could help explain our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although women are able to maintain adequate glycemic control using these treatment strategies, they can be difficult to implement, and concerns remain regarding the long-term effects of oral agents on the developing fetus. For these reasons, it would be beneficial to develop novel, safe, and effective strategies for GDM risk reduction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%